Beyond Color: The New Carbon Ink. Issue 46 (2nd May 2021) - Wang, Peng; Barnes, Benjamin; Huang, Zhongjie; Wang, Ziyi; Zheng, Ming; Wang, YuHuang
Abstract: For thousands of years, carbon ink has been used as a black color pigment for writing and painting purposes. However, recent discoveries of nanocarbon materials, including fullerenes, carbon nanotubes, graphene, and their various derivative forms, together with the advances in large‐scale synthesis, are enabling a whole new generation of carbon inks that can serve as an intrinsically programmable materials platform for developing advanced functionalities far beyond color. The marriage between these multifunctional nanocarbon inks with modern printing technologies is facilitating and even transforming many applications, including flexible electronics, wearable and implantable sensors, actuators, and autonomous robotics. This review examines recent progress in the reborn field of carbon inks, highlighting their programmability and multifunctionality for applications in flexible electronics and stimuli‐responsive devices. Current challenges and opportunities will also be discussed from a materials science perspective towards the advancement of carbon ink for new applications beyond color. Abstract : For more than 30 000 years, carbon ink has mainly been used as a black color pigment. However, the recent discovery of nanocarbon materials with remarkable physical and chemical properties enables new applications well beyond coloring. Recent advances in the development of nanocarbon inks and their emergent applications are reviewed, highlighting the fundamental and technical challenges as well as opportunities.